Design of Energy Transitive Platform Based On Smart Grid Via Blockchain - Rizvi, Jeffery Ali; Haque, Ibrar Ul; Haq, Fawadul; Aziz, Imran; Arshad, Jawad Ali (TECCIENCIA, 2022)
In this paper, we present our research, where residents purchase and sell locally produced renewable energy from each other. In this research work, we integrate block chain technology to create peer-to-peer market-places for distributed energy. First, we use a smart energy meter to measure various important parameters of electrical energy. In this proposed work, the initial measurements of the current are being performed with the help of hall effect sensor due to its accuracy. Second, supply voltage is calculated with the help of a transformer and DC biasing method. The apparent power is calculated by multiplying the measured current and voltage, and then the energy parameter is obtained. Using this smart energy meter, we obtain our desired parameters with sufficient accuracy of nearly 90 percent. These obtained parameters and results are directly uploaded to Amazon Web Server(AWS). We also develop an android app that connects with the AWS server. The designed system facilitates the users to perceive these electrical parameters on meter having built-in LCD display which shows all measured results including a number of units consumed, and billing information anywhere around the world. Finally, we develop a smart contract on Ethereum block chain which can transact the number of tokens according to the units sold or purchased by the users. The Consumer can set their selling rate through the app. Any user with this app is able to take their readings live to their smart phone.